Contextual modulation of pain in masochists: involvement of the parietal operculum and insula - Kamping, Sandra; Diesch, Eugen; Flor, Herta (Pain, 2016)
Pain can be modulated by contextual stimuli, such as emotions, social factors, or specific bodily perceptions. We presented painful laser stimuli together with body-related masochistic visual stimuli to persons with and without preferred masochistic sexual behavior and used neutral, positive, and negative pictures with and without painful stimuli as control. Masochists reported substantially reduced pain intensity and unpleasantness in the masochistic context compared with controls but had unaltered pain perception in the other conditions. Functional magnetic resonance imaging revealed that masochists activated brain areas involved in sensory-discriminative processing rather than affective pain processing when they received painful stimuli on a masochistic background. The masochists compared with the controls displayed attenuated functional connectivity of the parietal operculum with the left and right insulae, the central operculum, and the supramarginal gyrus. Masochists additionally showed negative correlations between the duration of interest in masochistic activities and activation of areas involved in motor activity and affective processing. We propose that the parietal operculum serves as an important relay station that attenuates the affective-motivational aspects of pain in masochists. This novel mechanism of pain modulation might be related to multisensory integration and has important implications for the assessment and treatment of pain.